Supine hypotensive syndrome of pregnancy: A review of current knowledge. Issue 3 (March 2022) - Massoth, Christina; Chappell, Daniel; Kranke, Peter; Wenk, Manuel
Abstract : N/A: Since the first description of supine hypotensive syndrome in the 1950s, its potentially detrimental effects on otherwise healthy women during late pregnancy have become a persistent challenge in obstetric practice. Establishing a 15° left lateral tilt during labour and caesarean section is a fundamental principle of obstetric care, universally adopted and upheld by current guidelines and recommendations. Reassessment of the original landmark studies in the light of current physiological and anatomical knowledge questions adherence to this standard in clinical practice. The modern practice of providing vasopressor support during caesarean delivery under neuraxial anaesthesia appears to negate any potential negative effects of a maternal full supine position. Recent MRI studies provide evidence as to the cause of supine hypotension and the physiological effects of different maternal positions at term. This review highlights current data on the acute supine hypotensive syndrome in contrast to traditional knowledge and established practice.